THE INFLUENCE OF TRAINING, COMMUNICATION, INFORMATION TECHNOLOGY AND LEADERSHIP ON IMPLEMENTATION OF KNOWLEDGE MANAGEMENT IN STATE CORPORATIONS - AKINYI, BENTER ALICE; Abok, Dr. Alice (IJRDO - Journal of Applied Management Science, 2015)
Knowledge management (KM) is a formalized, integrated approach to identifying andmanaging an organization's knowledge assets. The main purpose of this study was toinvestigate factors affecting the implementation of knowledge management in StateCorporations in Kenya. More specifically the study sought to evaluate the influence oftraining, communication, information technology and knowledge leadership onknowledge management. Studies done on knowledge management have focused oncomparisons on public and private sector use of knowledge. Others have examinedhow knowledge management practices are carried out in both the Public and PrivateSectors. To add the existing literature, the study investigated factors affecting theimplementation of knowledge management in state corporations. The studyconcentrated on the factors; Training, Communication, Information Technology andKnowledge Leadership. Descriptive research was used in the research. The targetpopulation was state Corporations in Kenya, while the study population was middle levelmanagers of the state corporation within the state Department of Agriculture. TheSample size was 100 middle level managers. Primary data was collected using aquestionnaire. A pilot test was conducted to establish the validity and reliability of thequestionnaire. Regression analysis was used to establish to what extent each variableaffects the dependent variable. Data presentation was done using tables, pie charts,averages, frequencies. Analysis was done using SPSS V.21 to assist in analyzing data.The study sought to establish the factors affecting knowledge managementimplementation in state corporations Case of State Department of Agriculture andwhether training, communication, information technology and knowledge leadership willaffect the implementation of knowledge management in state corporations. Results fromregression model of knowledge management implementation on organizational   leadership, communication, information technology and training revealed that thecoefficients for training, communication and information technology were significant at5% level of significance. Therefore, knowledge management implementation can bepredicted using training, communication and information technology. However, thecoefficient for organizational leadership was not significant.